Parameter Identification Problem in the discrete-time SIR Model - Valle, J. A. Mandujano; Madureira, A. Loureiro (Trends in Computational and Applied Mathematics, 2024)
We investigate the problem of determining time dependent parameters for discrete-time epidemiological compartmental models such as the Susceptible-Infected-Recovered (SIR). We show how to determine parameters based on minimal error type iterative schemes. Such methods involve the computation of the adjoint of the derivative operator of a nonlinear function. This is a nontrivial task that we accomplish by carefully crafting auxiliary problems. To show the efficiency of the method, we consider examples involving real COVID-19 data.